Midlife : a philosophical guide - Setiya, Kieran, 1976- (Princeton University Press, 2017)
Philosophical wisdom and practical advice for overcoming the problems of middle ageHow can you reconcile yourself with the lives you will never lead, with possibilities foreclosed, and with nostalgia for lost youth? How can you accept the failings of the past, the sense of futility in the tasks that consume the present, and the prospect of death that blights the future? In this self-help book with a difference, Kieran Setiya confronts the inevitable challenges of adulthood and middle age, showing how philosophy can help you thrive. You will learn why missing out might be a good thing, how options are overrated, and when you should be glad you made a mistake. You will be introduced to philosophical consolations for mortality. And you will learn what it would mean to live in the present, how it could solve your midlife crisis, and why meditation helps. Ranging from Aristotle, Schopenhauer, and John Stuart Mill to Virginia Woolf and Simone de Beauvoir, as well as drawing on Setiya's own experience, Midlife combines imaginative ideas, surprising insights, and practical advice. Writing with wisdom and wit, Setiya makes a wry but passionate case for philosophy as a guide to life.